POTENSI OBJEK WISATA PANTAI SIKABAU DI KECAMATAN KOTO BALINGKA KABUPATEN PASAMAN BARAT - Utami, Diza Sutia; Mariya, Sri (JURNAL BUANA, 2024)
Abstract This study aims to describe the potential possessed by the Sikabau Beach tourist attraction as seen from (1) Attractions (2) Amenities (3) Accessibility and efforts to develop Sikabau Beach attractions to attract visitors. This type of research is descriptive research with a qualitative approach using data collection techniques through observation, interviews, and documentation. Data analysis techniques start from data collection, data reduction, data presentation, drawing conclusions, and SWOT analysis. The results of the study showed (1) the main factors as the attractions or attractiveness of Sikabau beach in terms of strengths: The beauty of the marine natural scenery which is still very beautiful, in terms of weaknesses: the lack of adequate artificial attractions or rides. (2) Inadequate amenities to support tourism activities (3) Accessibility in terms of strength: the condition of the main route that is passed is very good and vehicle activity is not too busy¸in terms of weakness: the condition of the road leading to the Sikabau Beach tourist attraction is damaged. The main external factors in terms of opportunities: increasing people's economic income, in terms of threats: the environment, social problems, and competition. The right development strategy for the Sikabau Beach tourist attraction is to make good use of its potential and improve the quality of tourism management. and increase promotional activities by utilizing technology. Keywords: Tourism, Potential, Development, SWOT Analysis